The Nameless Crime: Reflections on the Origins and Development of the Concept of Genocide - Poghosyan, Narek (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
The term “genocide,” introduced by Raphael Lemkin, represents a groundbreaking milestone in the conceptualization and prevention of mass atrocities. Genocide is uniquely defined by the deliberate intent to annihilate specific human groups, earning its designation as the “crime of crimes” due to its profound legal and moral implications. Lemkin’s work unified disparate historical and linguistic precedents into a comprehensive legal framework, addressing the prior absence of a formal term for such heinous acts. Although genocide was once referred to as “a crime without a name,” historical evidence reveals that many cultures and languages had long acknowledged and described this phenomenon using terms such as Völkermord, folkmord, and “the murder of a nation.” Lemkin’s true innovation lay in synthesizing these fragmented concepts into a single, cohesive definition, firmly rooted in international legal discourse to promote recognition and accountability. This study explores the historical, linguistic, and legal evolution of the term “genocide,” emphasizing its enduring universal relevance and the challenges surrounding its classification in modern international debates.
Keywords: Armenian genocide